AB0914 Management of Gout in Different Clinical Specialties in Turkey. (9th June 2015) - Öztürk, M.A.; Mercan, R.; Gök, K.; Onat, A.M.; Kısacık, B.; Kimyon, G.; Balkarlı, A.; Kaya, A.; Çobankara, V.; Balcı, M.A.; Pamuk, Ö. N.; Çetin, G.Y.; et al.
Abstract : Background: In contrast to many European countries, patients can easily admit to secondary and tertiary centers without referral by the primary care in Turkey. Therefore we also compared the management options for gout preferred in different clinical specialties. Objectives: In this study we investigated how gout is treated in Turkey. Methods: 319 consecutive patients were included in this multicenter study (mean age 58.60±12.8 years, 44 females, 272 males). All patients filled a standard questionnaire. Results: 53 patients were first admitted to primary care (16.6%), 101 patients to orthopedics (31.7%), 29 patients to physical therapy and rehabilitation (9.1%), 70 patients to internal medicine (21.9%), 49 patients to rheumatology departments (15.4%), and 17 patients to other clinical specialties (5.3%). Among those 313 patients admitting to health care with acute gout attack, 40 patients were referred the patient to another center without any treatment (12.8%). Referral rate remarkably higher in the primare care (%28.8). NSAIDs were the most common drugs prescribed for acute attack (60.06%), followed by colchicine (58.15). Allopurinol was given in 12.8%, and steroids in 7.99% of patients during acute attack. Regarding long term treatment, 92 patients had never been treated with allopurinol (28.8%). 29.1% (37/127) patients having less than 2 attacks per year and 28.6% (55/192) of patients having two or more attacks per year had never been treated with allopurinol (p>0.05). Only 89 patients (27.9%) were treated with allopurinol by their first physicians, and 138 patients (43.3%) were treated with allopurinol later in a different specialty. Prescription of allopurinol was more common among the rheumatologists. Diet and life style modifications were recommended in 118 of the patients (37%) by their first physicians. 171 patients (53.6%) were later recommended diet and life style modifications during their follow up in a different clinical specialty (total 289 patients, 90.6%). Diet and life style modifications were recommended more commonly in rheumatology (41 patients, 83.7%). 183 (57.4%) were treated with colchicine by their first physicians, and 114 patients (35.7%) were treated with colchicine by a physician of different specialty (total 297 patients, 93.1%). Significantly more patients were treated with colchicine than with allopurinol during long term management (p<0.001). Conclusions: Treatment of gout appears suboptimal in primary care, and more than 25% of patients were referred without any treatment. Long term management also appears suboptimal in both primary care and among some specialists such as orthopedics. Only a minority of patients were recommended allopurinol and/or life style modifications by the doctors first diagnosed gout. Although long term treatment appears better among rheumatologist, still a considerable number of patients were not recommended uric acid lowering approaches in the rheumatology clinics. Disclosure of Interest: None declared